My father, the shape shifter Ang tatay kong nagpapalit-palit ng hugis - Sevilla, Maria Cecilia; Tejido, Jomike; Pastor, Boots S. Agbayani (Quezon City Lampara Publishing House, Inc., 2013)
"Luis father is away at sea to make their life as a family more comfortable. Because of this, Luis terribly misses his father. But Luis' father ahs an extraordinary quality that quenches his and his mother's loneliness as a result of their missing him. read in this story about the secret of Luis' father and how he manages to be with them despite the fact that he is far away."
Stories with moral values.
Lampara prize for Children's literature honorable mention 1/2011.
Text in English and Filipino.
Lampara prize for children's literature honorable mention 1/2011.
Keywords: Father and child -- Fiction